2020
DOI: 10.1002/jmv.26395
|View full text |Cite
|
Sign up to set email alerts
|

Human parechovirus are emerging pathogens with broad spectrum of clinical syndromes in adults

Abstract: Parechoviruses are emerging pathogens of humans often affecting the pediatric age group, with a growing line of evidence implicating them as agents of a broad spectrum of clinical syndromes in adults. However, because many clinicians are not familiar with the manifestation of the infections, they are not included in the list of diagnostic pathogens. Furthermore, due to the indistinguishable feature of the infection compared with other common pathogens, a large number of cases are likely to go unchecked. Some m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 79 publications
(380 reference statements)
0
6
0
Order By: Relevance
“…In China, it was found that children who were infected with PeV‐A have approximately 2.3 times increased chance of developing gastrointestinal symptoms in contrast to uninfected controls. This finding may be related to regional differences in the infection of the virus, as a recent review has suggested that disease incidence related to PeV‐A infection varies with a geographical region 84 . By genotype, we interestingly observed that PeV‐A5 and PeV‐A9 were inversely associated with gastroenteritis in children (OR 0.289, 95% CI: 0.099–0.843 and OR 0.149, 95% CI: 0.027–0.828, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In China, it was found that children who were infected with PeV‐A have approximately 2.3 times increased chance of developing gastrointestinal symptoms in contrast to uninfected controls. This finding may be related to regional differences in the infection of the virus, as a recent review has suggested that disease incidence related to PeV‐A infection varies with a geographical region 84 . By genotype, we interestingly observed that PeV‐A5 and PeV‐A9 were inversely associated with gastroenteritis in children (OR 0.289, 95% CI: 0.099–0.843 and OR 0.149, 95% CI: 0.027–0.828, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…This finding may be related to regional differences in the infection of the virus, as a recent review has suggested that disease incidence related to PeV-A infection varies with a geographical region. 84 understand prevalent patterns and strain-specific disease associations in the future. In addition, the frequent presence of PeV-A in healthy controls should not lead to the conclusion that PeV-A is not a critical pathogen that caused gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Human parechoviruses (HPeVs) are detected in children and adults and are associated with gastroenteritis and respiratory symptoms. Other symptoms including sepsis, meningitis, and encephalitis have been also reported(1,2).HPeVs are classified as species Parechovirus A, genus Parechovirus, in the family Picornaviridae. Parechovirus A is currently subdivided into 19 types, HPeV-1-19.…”
mentioning
confidence: 99%